Citizen Participation in Local Governance and Sustainability of Progammes (Global Journal of Science Frontier Research, 2015)
The purpose of this paper is to examine the need for citizen participation in local governance and sustainability of programmes in order to strengthen democracy and repositioning the local governments to meet the challenges of development. Any system of government is primarily constituted to provide services required by the citizens and this could be achieved effectively through participatory mechanisms. Hence, citizen participation in local government affairs will bring about development programmes in direct contact with the people and encourage them to become initiative and innovative. In this paper attempt was made to highlight the concept of participation, the structure of local government, participatory programmes for development and review of related experience for local citizen participation. On the basis of the finding, some recommendation such as well established democratic structure of local government to enhance citizenship participation, local officials should be engage in capacity building and innovative spirit to improve the delivery of services and also government should design a people orientated development programmes at all levels.
Keywords: participation; governance; sustainability